Local dependency in networks - Kudělka, Miloš; Zehnalová, Šárka; Horák, Zdeněk; Krömer, Pavel; Snášel, Václav (Zielona Góra: Uniwersytet Zielonogórski)
Many real world data and processes have a network structure and can usefully be represented as graphs. Network analysis focuses on the relations among the nodes exploring the properties of each network. We introduce a method for measuring the strength of the relationship between two nodes of a network and for their ranking. This method is applicable to all kinds of networks, including directed and weighted networks. The approach extracts dependency relations among the network`s nodes from the structure in local surroundings of individual nodes.
Keywords: complex networks; graph grammars; edge weighting; dependency